CHARACTER EDUCATION VALUES IN TREATISE DAWA' AL-QULUB MIN AL-'UYUB THE WORK OF SHEIKH MUHAMMAD BIN KHATIB LAGIEN - Baihaqi, Baihaqi; Syahrizal, Syahrizal; Buto , Zulfikar Ali (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
Character education goes hand in hand with Islamic education, because it has the same goal to form good morals, morals and ethics in students. The character values used as a starting point by the government of the Republic of Indonesia, which amount to 18 values, also have a connection with moral education in Islam. Sheikh Muhammad bin Khatib Langien wrote the book Risalah Dawa' al-Qulub Min al-'Uyub as a guide for Muslims to be a guide in building and forming noble morals in every human being. So, this research will examine the character education values in the treatise. This research is a descriptive qualitative research. The approach used is a literature study and uses an analytical descriptive approach. The primary data source in this research is the book of Risalah Dawa' al-Qulub Min al-'Uyub by Sheikh Muhammad bin Khatib Langien, and the secondary data sources are articles, books, and other sources related to the research title. The data collection technique uses the documentation method, with contents analysis as the data analysis technique. The results showed that in the book of Risalah Dawa' al-Qulub Min al-'Uyub by Sheikh Muhammad bin Khatib Lagien there are 21 important character values that students must have. These character values will lead them to success, success, and happiness in this world and the hereafter. These character values are as follows: sincerity, choosing discipline, loving knowledge, seriousness of learning, discipline, love of cleanliness, care for the environment, humble, communicative, compassion, good prejudice, taqwa, diligent worship, self-introspection, zuhud, patience, gratitude, tawakkal, rida, respect for teachers, and social care.